Pain in amyotrophic lateral sclerosis: Patient and physician perspectives and practices. Issue 1 (17th February 2016) - Stephens, Helen E.; Lehman, Erik; Raheja, Divisha; Yang, Chengwu; Walsh, Susan; Mcarthur, Donna B.; Simmons, Zachary
Abstract: Our objective was to better understand the experience and impact of pain on ALS patients in the U.S., and to survey ALS physicians on their pain assessment and management practices. Individuals with ALS were invited to complete an online survey of pain in ALS. ALS specialist physicians were sent an e-mail survey about their experiences in evaluating and managing patients' pain. Nearly 75% of patients with ALS reported significant pain, and most thought that ALS was the source of at least some of this pain. Pain intensity scores (mean 3.9/10) and pain interference scores (mean 4.3/10) were moderate on average, but nearly 80% of participants were using pain medication, including 22% using opioids. Nearly 25% of patients thought they needed stronger pain medication than they were receiving. Physicians generally assess and manage pain in ALS patients, but few use standardized assessment tools. Nearly two-thirds felt that there is a need for better pain management practices and more than one-third felt better training was needed. In conclusion, pain in patients with ALS is not always well controlled. Improvement in care may be facilitated by a more standardized approach to evaluation, and by additional education and training of ALS health care professionals.